USING ISLAMIC VIDEOS ON YOUTUBE TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' ENGLISH VOCABULARY MASTERY - Jasmia Jasmia; Chairil Anwar Korompot; Haryanto Atmowardoyo (Universitas Negeri Makassar, 2023)
This research aims to discover whether applying Islamic videos on YouTube might increase junior high school students' English vocabulary mastery. This research used a pre-experimental method with a one-group pre-test and post-test design and a questionnaire. The study population was 40 grade 8 students at SMP IT Nurul Fikri Makassar, South Sulawesi, in the 2021–2022 academic year. The respondents were recruited using a random sampling technique. The research instruments were a vocabulary test administered as a post-test and a pre-test, and a questionnaire. In analyzing the data, descriptive statistics was used. The post-test mean score was 84.5455; which shows that the post-test mean score was more significant than the pre-test mean score (68.6364). Of the percentage of students’ perceptions while using Islamic videos on YouTube, 85% answered yes, and only 15% answered no. Furthermore, the value of this study (0.001) was lower than the alpha level (0.05). These mean that H1 is accepted and H0 is rejected. Consequently, Islamic videos on YouTube could be used as medium to improve the students' English vocabulary mastery in grade 8 of SMP IT Nurul Fikri Makassar.